Predictors of children's conversational contingency - Danielle Matthews; David Pagmar; Kirsten Abbot-Smith (Language Development Research, 2022)
When in conversation, a child may respond to an adult’s turn in different ways: by saying something that acknowledges what was previously said, saying something that furthers the topic of the conversation, saying something off topic, or by not saying anything at all. Different types of responses like these have been investigated with typically developing preschoolers and older children with autism but we still understand relatively little about what predicts their use. With a longitudinal sample of 40 Swedish-speaking five-year-olds, we carried out three studies investigating which factors, internal and external to the child, were the best predictors of the above four different aspects of children’s conversational behaviour. In Study 1, we investigated the predictive value of broadly concurrent linguistic and cognitive measures and found that receptive vocabulary was related to appropriate conversation responses. In Study 2, we investigated the predictive value of environmental factors and found that later preschool entry was positively related to contingent responses in this relatively socially advantaged sample. Finally, in Study 3, we investigated the predictive value of social and cognitive factors measured in early development  and found no reliable relations. Together, these exploratory studies suggest that different aspects of children’s conversational skills may depend on strong lexical comprehension and may be facilitated by the caregiving environment.